Kualiti air tirisan: kajian kes di Ulu Yam dan Kuala Kubu Bharu, Selangor - Abdul Rahim Luqmanulhakim, Hashim Mohmadisa, Che Ngah Mohamad Suhaily Yusri, Nayan Nasir, Saleh Yazid (N/A, 2014)
Kualiti air tirisan: kajian kes di Ulu Yam dan Kuala Kubu Bharu, Selangor by Abdul Rahim Luqmanulhakim, Hashim Mohmadisa, Che Ngah Mohamad Suhaily Yusri, Nayan Nasir, Saleh Yazid,